Phenotypic evaluation and in silico ADMET properties of novel arylimidamides in acute mouse models of Trypanosoma cruzi infection - da Silva CF; Batista DDGJ; de Araújo JS; Cunha-Junior EF; Stephens CE; Banerjee M; Farahat AA; Akay S; Fisher MK; Boykin DW; Soeiro MDNC (Dove Medical Press, 2017)
Cristiane França da Silva,1 Denise da Gama Jaén Batista,1 Julianna Siciliano de Araújo,1 Edézio Ferreira Cunha-Junior,2 Chad E Stephens,3 Moloy Banerjee,4 Abdelbasset A Farahat,4,5 Senol Akay,4 Mary K Fisher,3 David W Boykin,4 Maria de Nazaré Correia Soeiro1 1Laboratory of Cellular Biology, 2Laboratory of Biochemistry of Trypanosomatids, Fundação Oswaldo Cruz, Rio de Janeiro, Brazil; 3Department of Chemistry and Physics, Augusta University, Augusta, 4Department of Chemistry, Georgia State University, Atlanta, GA, USA; 5Department of Pharmaceutical Organic Chemistry, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt Abstract: Arylimidamides (AIAs), previously termed as reversed amidines, present a broad spectrum of activity against intracellular microorganisms. In the present study, three novel AIAs were evaluated in a mouse model of Trypanosoma cruzi infection, which is the causative agent of Chagas disease. The bis-AIAs DB1957, DB1959 and DB1890 were chosen based on a previous screening of their scaffolds that revealed a very promising trypanocidal effect at nanomolar range against both the bloodstream trypomastigotes (BTs) and the intracellular forms of the parasite. This study focused on both mesylate salts DB1957 and DB1959 besides the hydrochloride salt DB1890. Our current data validate the high activity of these bis-AIA scaffolds that exhibited EC50 (drug concentration that reduces 50% of the number of the treated parasites) values ranging from 14 to 78 nM and 190 to 1,090 nM against bloodstream and intracellular forms, respectively, also presenting reasonable selectivity indexes and no mutagenicity profile predicted by in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET). Acute toxicity studies using murine models revealed that these AIAs presented only mild toxic effects such as reversible abdominal contractions and ruffled fur. Efficacy assays performed with Swiss mice infected with the Y strain revealed that the administration of DB1957 for 5 consecutive days, with the first dose given at parasitemia onset, reduced the number of BTs at the peak, ranging between 21 and 31% of decrease. DB1957 was able to provide 100% of animal survival, while untreated animals showed 70% of mortality rates. DB1959 and DB1890B did not reduce circulating parasitism but yielded >80% of survival rates. Keywords: Chagas disease, arylimidamides, experimental chemotherapy, in vivo assays